Impact of Childhood Trauma in Borderline Personality Disorder (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Patterns of instability in interpersonal interactions are a hallmark of borderline personality disorder (BPD), a complicated mental health disease, self-image, and affect, accompanied by impulsivity and emotional dysregulation. While the etiology Due to the multifaceted nature of borderline personality disorder (BPD), new research has linked traumatic experiences in early life may play a significant role in its development. This study aims to explore the link between traumatic experiences in childhood and the development of BPD. Through a comprehensive review of existing literature and empirical studies, this research examines the various forms experiences with physical, emotional, and mental trauma throughout childhood sexual abuse, neglect, and family dysfunction, and their potential impact on the neurobiological, psychological, and interpersonal factors in relation to borderline personality disorder. The ways in which traumatic experiences in childhood could bring about and sustain borderline personality disorder symptoms are also explored in this research., such as identity disturbance, affective instability, and difficulties in emotion regulation.